Platelet phenolsulphotransferase activity and 'abdominal migraine'. Issue 12 (December 1988) - Gibb, C; Glover, V; Gilbertson, N; Bentley, D; Sandler, M
Abstract : Low platelet phenolsulphotransferase activity has been reported in adult patients with dietary sensitive migraine. Platelet activity of this enzyme was therefore measured in children having 'abdominal migraine' with probable dietary trigger and in controls. No significant difference was found in activity between the two groups. There was no significant correlation between platelet phenolsulphotransferase activity and age.